Placental extracts regulate melanin synthesis in normal human melanocytes with alterations of mitochondrial respiration. (30th January 2019) - Yoshimoto, Satoshi; Ohagi, Yoshiaki; Yoshida, Moemi; Yanagi, Hiroki; Hibino, Sawako; Ichihashi, Masamitsu; Ando, Hideya
Abstract: Placental extracts have been widely used as skin lightening agents in the Japanese cosmetic market. Here, we show that placental extracts contain factors that can decrease or increase melanin synthesis by normal human melanocytes in vitro in possible association with mitochondrial respiration. When normal human melanocytes were treated with a whole porcine placental extract, melanin synthesis was decreased. In contrast, a porcine placental extract in which exudates and insoluble materials including lipids had been removed increased melanin synthesis. In addition, the amount of tyrosinase, the enzyme critical for melanin synthesis, changed in accordance with the alteration of melanin synthesis. Interestingly, the amount of manganese‐dependent superoxide dismutase (MnSOD), a mitochondrial‐resident antioxidant enzyme, was increased when melanin synthesis was decreased by the whole placental extract. Mitochondrial respiration and glycolysis also changed following treatment with the placental extracts. These results suggest that placental extracts contain factors that can increase or decrease melanin synthesis by normal human melanocytes and that mitochondrial function may be associated with the placental extract‐induced regulation of melanogenesis.